Retinol Has a Skin Dehydrating Effect That Can Be Improved by a Mixture of Water-Soluble Polysaccharides - James V. Gruber; Venera Stojkoska; Jed Riemer (Cosmetics, 2020)
It is common that retinoids used in skincare can cause skin dryness, irritation and redness which is a complaint for the use of these molecules in skincare formulations. Objective: to investigate the influence of a mixture of polysaccharides to improve retinol-based formulations in a 12-day inner volar forearm study. Methods: in total, 22 inner volar forearms were treated over a 12-day topical application of a Placebo formulation containing 0.5% retinol verses a formulation containing 0.5% retinol and 3.0% of a complex of polysaccharides. Application occurred 2X/day in the morning and evening. Skin testing included barrier disruption, erythema, and skin hydration. After a 3-day regression of treatment, skin hydration was measured again. Results: the 0.5% retinol Placebo formulation showed a significant impact on skin dehydration compared to untreated control or polysaccharide-treated areas. The formulation containing retinol and 3.0% of the polysaccharides, maintained skin hydration levels comparable to the untreated control. Neither formulation had a statistically significant impact on skin erythema or barrier disruption. After the 3-day regression, the polysaccharide mixture continued to demonstrate significant moisturization benefits superior to the untreated and active-treated sites. Conclusions: a mixture of polysaccharides was able to mitigate the short-term skin drying effects of retinol and continued to moisturize the skin after a 3-Day regression.